Verification of heart rate monitor using PPG pulse sensor - Mohd Saad, Wira Hidayat; Abd Salam, Nurul Akmal; Tan, Kien Leong; Baharom, Siti Nor Atikah (Research India Publications, 2014)
This is an effort made which describes the design verification of heart rate display device developed by using a PIC microcontroller. The sensor use to detect heart rate is an optical sensor and the calculated value of the heart rate reading is displayed by using an LCD display. The analyses of the photoplethysmogram signals captured by using an optical sensor and the signal process using a microcontroller chip are explained briefly. Heart rate of the subject is measured from the finger by tightly placing the sensor on the tips of the finger and on the ring position. The heart rate readings are then averaged and displayed on a text based LCD and the reading is refreshed in every ten second. The concept of the development is very promising and can be applied in many health care based applications. The result is verified by using two hundred different samples taken randomly and its show a very minimal error.